Flow cytometric measurement of respiratory burst activity and surface expression of neutrophils for septic patient prognosis. Issue 4 (7th August 2015) - Bae, Mi Hyun; Park, So Hee; Park, Chan‐Jeoung; Cho, Eun‐Jung; Lee, Bo‐Ra; Kim, Young Jin; Park, Sang Hyuk; Cho, Young‐Uk; Jang, Seongsoo; Song, Dong‐Keun; Hong, Sang‐Bum
Abstract : Background: The hyperinflammation that begins with sepsis is essential for eradicating infection but also causes hypoperfusion and organ failure. To understand the innate immune status of septic patients, the functional and phenotypic changes of neutrophils during sepsis and their clinical implication were studied. Methods: Seventy‐four patients who were admitted to intensive care unit due to severe sepsis or septic shock were enrolled. Surface antigens of neutrophils (CD64, CD10, and CD16) were detected by flow cytometry. Respiratory burst activity (RBA) was measured by flow cytometry using 2′, 7′‐dichlorofluorescein diacetate and phorbol‐12‐myristate‐13‐acetate. The parameters were serially examined at Days 1 and 8 in septic shock patients. Results: High CD64 and low CD10 and CD16 on Day 1 was associated with sepsis severity ( P = 0.003, 0.017, and 0.007, respectively). On Day 1, RBA and CD64 were higher in survivors than in nonsurvivors of septic shock patients ( P = 0.012 and 0.027, respectively), and on Day 8, CD10 and CD16 were higher in survivors than in nonsurvivors ( P = 0.019 and 0.036, respectively). High RBA and high CD64 on Day 1 showed low 28‐day mortality in univariate analysis ( P = 0.018 and 0.034, respectively). In multivariate analysis, RBA maintained statistical significance ( P = 0.042) but CD64 revealed only a tendency ( P = 0.064). Conclusions: Neutrophil surface antigen (CD64, CD10, and CD16) could reflect sepsis severity. High CD64 expression and high RBA at early phase of sepsis might be associated with better prognosis, whereas high expression of CD10 and CD16 at late phase of sepsis might be associated with better prognosis. © 2015 International Clinical Cytometry Society